(untitled) (MAUSAM, 1986)
In this study moisture incursion in the Arabian Sea has been monitored during the onset, active and withdrawal phase of the summer monsoon (May-Sept 1984) using sea surface temperature anomalies This study shows that tongue of moist air reached south. Peninsula about 20 days ahead of the normal onset of monsoon and continued to be ahead by 12-14 day even after Its setting. During the withdrawal phase it has been observed that moist air starts with drawing from north Arabian Sea by third week of September replaced by dry continental air mass which continued to move southward pushing further south the moist air and the monsoon.